A highly parallel simulation of patient‐specific hepatic flows. (3rd March 2021) - Lin, Zeng; Chen, Rongliang; Gao, Beibei; Qin, Shanlin; Wu, Bokai; Liu, Jia; Cai, Xiao‐Chuan
Abstract: Computational hemodynamics is being developed as an alternative approach for assisting clinical diagnosis and treatment planning for liver diseases. The technology is non‐invasive, but the computational time could be high when the full geometry of the blood vessels is taken into account. Existing approaches use either one‐dimensional model of the artery or simplified three‐dimensional tubular geometry in order to reduce the computational time, but the accuracy is sometime compromised, for example, when simulating blood flows in arteries with plaque. In this work, we study a highly parallel method for the transient incompressible Navier–Stokes equations for the simulation of the blood flows in the full three‐dimensional patient‐specific hepatic artery, portal vein and hepatic vein. As applications, we also simulate the flow in a patient with hepatectomy and calculate the S (PPG). One of the advantages of simulating blood flows in all hepatic vessels is that it provides a direct estimate of the PPG, which is a gold standard value to assess the portal hypertension. Moreover, the robustness and scalability of the algorithm are also investigated. A 83 % parallel efficiency is achieved for solving a problem with 7 million elements on a supercomputer with more than 1000 processor cores. Abstract : We study a highly parallel method for the transient incompressible Navier–Stokes equations for the simulation of the blood flows in the full three‐dimensional patient‐specific hepatic artery, portal vein and hepatic vein. The robustness and scalability of the algorithm are also investigated on a supercomputer with more than 1000 processor cores. As applications, we also simulate the blood flows in the portal vein before and after a left hepatectomy and calculate the PPG. From the cover graph we can see that the values of the pressure, velocity and WSS are all within the normal ranges before the hepatectomy. However, they are beyond the normal range after the hepatectomy. The algorithm has paved a path for our next step study for providing surgery planning.